INCIDENCE OF FRACTURE IN SMALL RUMINANTS: A RETROSPECTIVE STUDY - FAROOQ, AA; KHAN, MA; AKBAR, H; LASHARI, MH; INAYAT, S; JAVID, MA; SALEEM, MU; MURTAZA, S; SHAH, MH; BASIT, MA; et al. (Biological and Clinical Sciences Research Journal, 2024)
The availability of information or data regarding various affections forms a powerful tool for rendering appropriate treatment. The present study was designed to acquire data on fracture in small ruminants. This study will act as a base for policymakers to implement future projects in orthopedics for different species of animals. All the cases of bone affection at the indoor surgery clinic, Department of Veterinary Surgery, the University of Veterinary and Animal Sciences, Lahore, for four years from 2016 to 2019 were enrolled in the study. The diagnosis was based on the clinical history, signs, and clinical examination and by radiograph. Treatment as medicinal or surgical interventions was provided wherever feasible. The data concerning species, sex, age, bone, type of fracture, and cause were compiled and analyzed by using the Chi-Square test. The overall incidence of fracture was found to be 4.47%. Caprine was the most common (96.136%) subject exposed to bone fracture. The fracture incidence was highest between 7 and 12 months of age, 76.40% in goats and 67.857% in sheep. Furthermore, male subjects were more prone to fracture (69.617%) and (15.405%) than females (30.383%), and (6.527%) in goats and sheep, respectively. The metacarpal (43.953%) in goats was affected bone most commonly with fracture, followed by the metatarsal (28.319%), tibia fibula (14.159%), radius–ulna (11.504%), humerus (1.475%), femur (0.590%). While in the case of sheep, metacarpal (40.476%) was followed by metatarsal (22.619%), tibia-fibula (26.190%), and radius–ulna (10.714%). Moreover, in bovines, the overall incidence of fracture was 1.82%. Similarly, in equines, fractures were mostly of radius-ulna (16.66%) and metatarsal (23.33%). The most common site of the fractures was located in the mid-shaft of a bone. Trauma (46.018%) was the most common cause of a fracture in goats, while in sheep, it fell from a height (40.476%). It was concluded that the metacarpal bone fracture was the most common fracture in goats than other animals.